A Functional Radiological and Soft Tissue Classification to Predict Outcomes in Orbital Fracture Surgery in a Multidisciplinary “Real-World” Setting - Yang, Elizabeth; Chan, Shu-Yi Claire; Al-Omari, Yara; Ward, Louise; Yap, Timothy E.; Jhass, Aneka; Pancholi, Ravi; Aziz, Ahmad; Bentley, Christopher Richard; Perry, Michael; Lee, Vickie (Frontiers in Surgery, 2021)
Purpose: The decision for open reduction and internal fixation (ORIF) of orbital fractures is usually based on clinical severity and soft tissue and bony findings. This study aimed to identify prognostic factors for a successful surgical outcome. Materials and Methods: We included all orbital fractures treated by ORIF referred to the Ophthalmology clinic for assessment over a 12-year period. A successful outcome was defined as (i) a single operation, (ii) improved diplopia and globe position at 6 months, (iii) no surgical complications, and (iv) patient satisfaction. Data was collected on presenting symptoms, orthoptic measurements, time interval from injury to surgery, fracture geometry and involvement of internal, and external bony landmarks. Univariate and multivariate regression was used to identify predictive factors for success. Results: There were 143 cases with median age 35.4 years and 81.8% (117/143) male. 51% (73/143) were complex fractures involving multiple orbital walls. 63.6% (91/143) achieved significant improvement in both enophthalmos and diplopia at 6 months. 15.3% (22/143) had significant preoperative soft tissue or neurogenic injury. 11.8% (17/143) required orbital plate repositioning or removal. 1.4% (2/143) developed orbital haematoma and 4.2% (6/143) had cicatricial entropion. Pre-operative nerve or muscle damage (OR 0.05, p = 0.01) and infraorbital fissure fracture (OR 0.38, p = 0.04) were associated with poor outcomes, whereas an intact posterior ledge was associated with successful outcomes (OR 3.03, p = 0.02). Conclusion: Careful ocular motility evaluation to ascertain neurogenic injury and muscle compartment syndrome, and radiological analysis of the integrity of the posterior ledge and the inferior orbital fissure can facilitate management and expectations of ORIF surgery.